Flight muscle and flight activity of melon fly, Bactrocera cucurbitae (Diptera: Tephritidae) - Ferdousi, Farhana; Sultana, Shanjida; Akter, Tangin; Roy, Pinakshi; Begum, Shefali (Dhaka University Journal of Biological Sciences, 2021)
The flight activity and flight muscle of the melon fly, Bactrocera cucurbitae (Coquillett) (Diptera: Tephritidae) were observed. The Tethered technique was used to observe the flight activity in this study. The flight activity, and wing and flight muscles were compared between male and female melon flies. The results indicate that the female was relatively better and strong flier than the male. The mean duration of the flight activity of the females was 13.90 min/hour and of the males was 7.12 min./hour. The mean length, width, volume of wings of the males were 6.07 mm, 2.67 mm and 10.99 mm³, respectively. On the other hand, the mean length, width and volume of the wings of females were 7.07 mm, 2.87 mm and 15.60 mm³, respectively. In case of wing muscles, the mean volume of dorsal longitudinal muscle (DLM) in male and female was found 5.20 mm³ and 5.67 mm³, respectively. The mean length of flight wing muscle of male and female was 2.22 and 2.23 mm, respectively and the mean breadth of male and female was 1.65 and 1.77 mm, respectively. Dhaka Univ. J. Biol. Sci. 30(2): 179-185, 2021 (July)